(untitled) (Atti del Sodalizio Glottologico Milanese, 2017)
The paper deals with the syntax of preverbs, postpositions (including postpositional phrases) and existential quantifiers/ negative polarity items in Hittite within the Minimalist Program. Their in-situ and ex-situ positions are determined. The in-situ position of both PP and preverbs is that of the complement of VP whereas existential quantifiers/NPIs normally land by head movement in eQ, a dedicated exitential quantifier projection which is located in the TP layer. KEYWORDS: syntax, preverbs, postpositions, indefinite pronouns, Hittite